Analysis of Total Dissolved Solids Levels at Water Treatment Plant 2 of PT Hanarida Tirta Birawa: Analisis Kadar Total Dissolved Solid Pada Instalasi Pengolahan Air 2 PT Hanarida Tirta Birawa - Naafi’ Putri Pertiwi; Munawar Ali (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This study aims to analyze the Total Dissolved Solid (TDS) levels at Water Treatment Plant 2 (IPA 2) of PT Hanarida Tirta Birawa which uses the Pelayaran River as a source of raw water. The results of the analysis show that the TDS value of raw water tends to be high at 01.00 and 07.00 compared to 13.00. After the processing process, most of the values ​​still meet the quality standards, but there is an increase in TDS. The increase in TDS values ​​after processing can occur due to the use of coagulant doses that may be too high. It is recommended to optimize the water treatment process by reducing the coagulant concentration to increase the efficiency of TDS removal. It is expected that the quality of the processed water can be improved and meet drinking water quality standards better.